1972
DOI: 10.1085/jgp.59.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Studies of Oxidative Metabolism in Isolated Papillary Muscle of the Rabbit

Abstract: The fluorometric technique for measuring the levels of reduced pyridine nucleotides was used to study oxidative metabolism in isolated rabbit papillary muscle at 23 0 C. The 100 % standard level of tissue fluorescence was defined as that measured for muscles resting in oxygenated 10 mM pyruvate solution. This level increased 15% with anoxia and decreased 45 % with stimulation in substrate-free solution. Thus, about one-half of the standard tissue fluorescence was metabolically labile and this labile fraction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 32 publications
6
32
0
Order By: Relevance
“…The effects of pyruvate on the resting (NADH) fluorescence of rabbit papillary muscles was first described by Chapman [217]. Subsequently, Chapman and Gibbs [97], in myothermic studies on papillary muscles, reported that increments of 70% or more in the resting heat rate of quiescent papillary muscles were possible, and it was noted that pyruvate also had pronounced effects on mechanical output.…”
Section: Modifiers Of Basal Metabolismmentioning
confidence: 99%
“…The effects of pyruvate on the resting (NADH) fluorescence of rabbit papillary muscles was first described by Chapman [217]. Subsequently, Chapman and Gibbs [97], in myothermic studies on papillary muscles, reported that increments of 70% or more in the resting heat rate of quiescent papillary muscles were possible, and it was noted that pyruvate also had pronounced effects on mechanical output.…”
Section: Modifiers Of Basal Metabolismmentioning
confidence: 99%
“…The NADH/NAD + ratio may either increase [54,55] or decrease [52,53] in skeletal muscle during rest-to-work transition and is essentially constant in heart during transition to a higher work [56,44].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Furthermore, fluorescence from respiratory chain (i.e. mitochondrial) NADH is enhanced over the fluorescence from cytoplasmic NADH to the point that fluctuations in cytoplasmic NADH contribute little to the fluorescence signal (J6bsis & Duffield, 1967;Chapman, 1972;O'Connor, 1977). In practice NADH is excited by focusing U.V.…”
Section: Introductionmentioning
confidence: 99%